Determining antioxidant activities of lactobacilli by cellular antioxidant assay in mammal cells. (December 2015) - Xing, Jiali; Wang, Gang; Zhang, Qiuxiang; Liu, Xiaoming; Yin, Boxing; Fang, Dongsheng; Zhao, Jianxin; Zhang, Hao; Chen, Yong Q.; Chen, Wei
Highlights: Three cell models were used to assay the CAA value of CFS and SS of lactobacilli. Three cell lines were associated in determining the CAA values of CFSs and SSs. No correlation between the AA of CFSs and SSs of test lactobacilli in the CAA assay. Anti-oxidative properties of CFSs and SSs in CAA assay are strain-specific. Abstract: Among the beneficial effects of Lactobacillus spp., the common mechanism underlying health protection is believed to be related to antioxidant activity. The antioxidant activities of cell-free suspension (CFS) and strain suspension (SS) of 13 Lactobacillus strains derived from 4 species ( L. rhamnosus, L. acidophilus, L. casei, and L. fermenti ) were determined. The correlation of CFSs and SSs in different cell lines, as well as the correlation among the three cell models (RAW264.7, Caco-2, and EA.hy926 cell lines), were compared. All CFSs and SSs of lactobacilli showed that they significantly inhibited the production of intracellular reactive oxygen species without creating obvious cytotoxic effects in the three mammal cell lines. These results suggested that RAW264.7, Caco-2, and EA.hy926 cell lines could be used as cell models to assay the cellular antioxidant activity of CFS and SS of lactobacilli. Thus, lactobacilli and by-products are a potential source of natural antioxidants and to reduce oxidative stress.